Development of an implementation-focused network to improve healthcare delivery as informed by the experiences of the SCI knowledge mobilization network. (30th September 2019) - Wolfe, Dalton L.; Walia, Saagar; Burns, Anthony S.; Flett, Heather; Guy, Stacey; Knox, Jason; Koning, Cyndie; Laramée, Marie-Thérèse; O'Connell, Colleen; Scovil, Carol Y.; Wallace, Michelle; ,
Abstract : Context: Implementing research findings into clinical practice is challenging. This manuscript outlines the experiences and key learnings from a network that operated as a community of practice across seven Canadian Spinal Cord Injury (SCI) rehabilitation centers. These learnings are being used to inform a new implementation-focused network involving SCI rehabilitation programs based in Ontario, Canada. Methods: The SCI KMN adapted and applied implementation science principles based on the National Implementation Research Network's (NIRN) Active Implementation Frameworks in the implementation of best practices in pressure injury and pain prevention and management. Results: The SCI KMN was successful in implementing best practices in both pressure ulcer and pain prevention and management across the various participating sites. Other key objectives met were building capacity in implementation methods in site personnel so that project scaling could occur with these skills and expertise applied to numerous other initiatives. Additionally, various papers, abstracts and conference presentation as well as an implementation guide were disseminated to inform the field of implementation science. Conclusion: The key lessons learned from this experience are being used to develop a new implementation-focused network. Features felt to be especially important for the SCI KMN includes a highly representative governance structure, the use of indicators within an overall evaluation framework and the systematic application of implementation processes with shared learnings supporting each site.